Factors Affecting Participation level on extension of dairy farmer in Enrekang Regency - S. Baba; . Isbandi; T. Mardikanto; . Waridin (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2011)
Farmers’ participation in agricultural extension can improve the relevancy between extension services and the farmer needs. There are many factors that may affect farmers’ participation in agricultural extension. The aim of this study was to understand characteristic influence and perception of farmers onto extension towards level of farmer participation in agricultural extension. Method applied was non experimental design survey with structural equation model analysis and analysed using Lisrel 8,3 application. The number samples were which were obtained from two areas, 103 that divided by two area, central area 57 samples and non central area 46 samples. Exogenous variable was farmers’ characteristics and endogenous variable were farmers’ perception and level of farmers’ participation in agricultural extension. The analysis of structural model indicated that farmers’ characteristics negatively correlated with farmers’ perception to agricultural extension in which the higher levels of age, cosmopolite, and formal education. Similarly, farmers’characteristics negatively affected either directly or indrectly farmer participation, meaning the the higher levels of age, formal education, and cosmopolite the lower participation level on the extension. Effects of perception on participation was significantly negative, indicating that the higher perception the higher participation in the extension. Quality of extension services e.g. extension materials, method used, and capacity of extension officers must be improved. Current extension services can only meet the needs of young farmers. The more complex the farmers’ needs the more unlikely the extension to meet famers’ needs.